Indexing of the Qur’an: Cairo, Egypt Dhu al Hijjah 15-16, 1409/ July 18-19, 1989 (American Journal of Islam and Society, 1989)
A seminar was organized by the International Institute of Islamic Thought,on Dhu al Hijjah 15-16, 1409/July 18-19, 1989, at Zamalek, Cairo, to discussthe indexing of the Holy Qur’an.In the first session, research papers and repom by members of the seminarwere presented. In the second and third sessions, the papers were discussedfrom different angles. During the closing session, the recommendationsprepared by the drafting committee were discussed.First: Project ObjectivesThe International Institute of Islamic Thought took the responsibilityfor the task of the Islamization of knowledge. The natural approach wouldbe to make the two main sources of Islamic knowledge-the Qur’an and theSunnah-accessible to research scholars in the humanities and social sciences.This project aims - during this stage-at analyzing the contents of the Qur‘anicverses to classify them according to the different branches of knowledge,and to arrange them under suitable headings, in order to make it easy forresearch scholars to find the verses they want in the fields of the humanitiesand social sciences.Second: Indices and ConcordancesParticipants in the seminar exchanged consultations regarding whetherit is suitable to compile a list of topics (index) first, then proceed with theclassification process accordingly, or should the classification be completedfirst on the basis of topics to be found, followed by the cornpilafion of an index.After completing the discussion, it was decided to follow both approachessimultaneously as indicated below: ...